2012
DOI: 10.7869/tg.2012.70
|View full text |Cite
|
Sign up to set email alerts
|

Community acquired secondary bacterial peritonitis in a tertiary hospital of South India: an audit with special reference to peritoneal fluid culture

Abstract: Background: This study was conducted to elucidate the spectrum of community acquired acute bacterial peritonitis, the role of microbiological culture in its management and other

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 23 publications
7
14
0
Order By: Relevance
“…Around 18.4% of cultures were positive for Klebsiella which was comparable to the study by Ramakrishnaiah et al (18.29%) 6. Acinetobacter (0.04%) was the least cultured organism in my study, which was comparable to the study by Ramakrishnaiah et al (5.3%) 6.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…Around 18.4% of cultures were positive for Klebsiella which was comparable to the study by Ramakrishnaiah et al (18.29%) 6. Acinetobacter (0.04%) was the least cultured organism in my study, which was comparable to the study by Ramakrishnaiah et al (5.3%) 6.…”
supporting
confidence: 89%
“…Only Afridi et al, gave rectal perforations in his study, where he showed only one of his subjects having a rectal perforation 10. None of the patients in this study had a rectal perforation.The peritoneal fluid culture from 64.7% of patients were positive for cultures, of which the most common microbe isolated was E. coli (27.6 %), which was also the most common organism in the study by Ramakrishnaiah et al (34.46%) 6. Around 18.4% of cultures were positive for Klebsiella which was comparable to the study by Ramakrishnaiah et al (18.29%) 6.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Even in mild very common surgical emergency such as appendicitis frequently seen in young adults, in whom the outcomes are usually good, in elderly this disease is becoming more prevalent and, it is far more serious requiring an early diagnosis and treatment, and even so associated with a mortality rate of about 3%, and post-operative complication around 20% 20 .…”
Section: Discussionmentioning
confidence: 99%